Analisis Pengaruh Integritas dan Kepuasan terhadap Loyalitas Guru di Kupang: The Analysis of Integrity and Satisfaction Effect on Teacher Loyalty in Kupang - Franky Franky; Thomas Budiman (Society, 2021)
Kupang is a city where teacher competence is still low. The government has disbursed quite a lot of funds for teacher development in Kupang. It is unfortunate if the teachers who have been fostered do not have high loyalty to move to other schools or leave the area. It is suspected that loyalty is influenced by teacher satisfaction and integrity. Satisfaction can include satisfaction with salary, workload, leadership, co-workers, awards, regulations, and facilities. If the components influence of satisfaction and integrity on teacher loyalty in Kupang can be found, then policies to increase loyalty can be pursued. This research aims to analyze the distribution of teachers in Kupang based on their loyalty, analyze the distribution of teachers in Kupang based on their general satisfaction, the distribution of teachers in Kupang based on their integrity, and the effect of integrity and satisfaction on teacher loyalty in Kupang. This research was conducted based on 141 teachers in Kupang who were selected by purposive sampling. The method used for data analysis is Partial Least Square (PLS) and Distribution Table. The data analysis found that 39% of respondents had low loyalty, and 61% had high loyalty; 48.2% of respondents had low general satisfaction and 51.8% had high satisfaction, 44% had low integrity, and 56% had high integrity. Variables that influence loyalty are integrity, satisfaction with salary, school rules, and co-workers. The higher the integrity and satisfaction component of salaries, regulations, and co-workers, the higher the loyalty of teachers in Kupang.